1998
DOI: 10.1139/v97-209
|View full text |Cite
|
Sign up to set email alerts
|

Coriolis coupling constants and inertial defect of B2F4 by ab initio calculations and the iterative method

Abstract: Structural parameters, harmonic frequencies, and force constants of B2F4 were obtained in internal coordinates from ab initio RHF calculations with the 6-311G* basis set. The results obtained are used to calculate the Coriolis coupling constants and the inertial defect for 10B2F4 and 11B2F4 and to compare these values with those obtained by using the autoconsistency method. Both the ab initio and the iterative force fields, despite some significant differences, reproduce the vibrational wave numbers equally we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently, it was found that only with large basis sets at the HF level or including correlation effect can the planar structure of B 2 F 4 be a minimum and lower in energy than the staggered structure. 24, 26,32,33 To judge if a structure is a minimum or a transition state, vibrational frequency analysis is always necessary. However, few studies have performed vibrational frequency analysis on both conformations of B 2 F 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that only with large basis sets at the HF level or including correlation effect can the planar structure of B 2 F 4 be a minimum and lower in energy than the staggered structure. 24, 26,32,33 To judge if a structure is a minimum or a transition state, vibrational frequency analysis is always necessary. However, few studies have performed vibrational frequency analysis on both conformations of B 2 F 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier ab initio calculations at the Hartree−Fock (HF) level with small basis sets indicate that the eclipsed structure of B 2 F 4 is higher in energy than the staggered structure, while semiempirical calculations indicate a reverse energy order, in accordance with experimental findings. Recently, it was found that only with large basis sets at the HF level or including correlation effect can the planar structure of B 2 F 4 be a minimum and lower in energy than the staggered structure. ,,, To judge if a structure is a minimum or a transition state, vibrational frequency analysis is always necessary. However, few studies have performed vibrational frequency analysis on both conformations of B 2 F 4 .…”
Section: Introductionmentioning
confidence: 99%